Thermal fatigue life prediction of particle reinforced composites. (May 2014) - Liu, X. Q.; Ni, X. H.; Cheng, Z. G.; Fu, Y. W.
<x content-type="archive" xml:space="preserve">Abstract</x> This article proposes a thermal fatigue life prediction model for particle reinforced composites. First, a three-phase model was used to determine the effective eigen strain of a two-phase element formed by an ellipsoidal matrix shell surrounding an ellipsoidal particle, and then the disturbance strain in the two-phase element caused by thermal inconsistency was obtained. If the average stress in the effective medium was considered as vanished, the thermal stress field in the matrix and particles was obtained by considering random orientation of two-phase elements. Second, based on the interface cracks propagating around the ellipsoidal particles, the strain energy release rate was examined. When the strain energy release rate reached the critical value of the matrix, the debonding stress was determined. The subtending angle and initiation crack length were available. Finally, according to the low cycle fatigue crack growth rate formation, the thermal fatigue life was computed. The results show that the bigger the thermal stress is, the smaller the thermal fatigue life is, indicating that thermal fatigue life is an exponential function of crack initiation length and critical length.